Synthesis of novel papulacandin D analogs and evaluation of their antifungal potential - Ana Carolina Oliveira Bretas; Thiago Belarmino de Souza; Beatriz Borelli; Suzana Johan; Ricardo José Alves (Universidade de São Paulo, 2020)
Systemic fungal infections are a growing problem in contemporary medicine and few drugs are licensed for therapy of invasive fungal infections. Differences between fungi and humans, like the presence of a cell wall in fungal cells, can be explored for designing new drugs. (1,3)-β-D-glucan synthase, an enzyme that catalyzes the synthesis of (1,3)-β-D-glucan, a structural and essential component of the fungal cell wall, is absent in mammals and this makes it an excellent target for the development of new antifungal agents. Papulacandins are a family of natural antifungal agents targeting (1,3)-β-D-glucan synthase. In this study we describe the synthesis and biological evaluation of two new Papulacandin analogs as potential (1,3)-β-D-glucan synthase inhibitors.